Kepemimpinan Pendidikan berbasis Sunnah: Membaca Jejak Pemikiran Umar bin Khattab - Nana Rismana; Nur Cholid (Universitas Muhammadiyah Prof Dr Hamka, 2024)
Education is a human right and a basic need in everyday life. The purpose of this research is to determine the educational philosophy of Caliph Umar bin Khattab. This research uses exploratory descriptive research techniques. Library research is the research method used. Primary and secondary data sources were used. The data collection process was carried out by reading previous publications or studies related to Umar bin Khattab's ideas. The findings of this research show that during Umar's time education included an exchange of important elements, such as funding and vision. Umar's educational efforts to reintroduce Islam to those who dissented were considered effective. From an educational perspective, the criteria used to select teachers during the reign of Umar bin Khattab were in line with the scientific qualifications of educators. During the time of Umar bin Khattab, lectures, talaqi, and halaqah were teaching techniques. During Umar Bin Khattab's time, education was provided through the curriculum. This can be seen in the framework of the educational organization founded by Umar Bin Khattab, namely establishing mosques as places of learning.